Activation-induced cytidine deaminase-mediated hypermutation in the DT40 cell line - Arakawa, Hiroshi (The Royal Society, 2008)
Depending on the species and the developmental stage of B cells, activation-induced cytidine deaminase (AID) triggers immunoglobulin (Ig) gene diversification by gene conversion, hypermutation or switch recombination. The bursal B cell line DT40 usually diversifies its rearranged Ig light chain (IgL) gene by gene conversion, but disruption of the RAD51 gene paralogues or deletion of the ψV conversion donors induces hypermutation. Although not all aspects of somatic hypermutation can be studied in DT40, the compact size of the chicken IgL locus and the ability to modify the genome by targeted integration are powerful experimental advantages. We review here how the studies in DT40 contributed to understanding how AID initiates Ig gene diversification and how AID-induced uracils are subsequently processed by uracil DNA glycosylase, proliferating cell nuclear antigens and error-prone polymerases. We also discuss the on-going research on the Ig locus specificity of hypermutation and the possibility of using hypermutation for the artificial evolution of proteins and regulatory sequences in DT40.